An Analysis of Semantic Meaning Found in Ted Talks Instagram Caption - Syah Putra, Aidil; Alyani, Elsa; Melyana, Mita; Sari, Sekar Wulan (OJS Universitas Muhammadiyah Gresik, 2024)
Language stands out as the primary and most crucial tool for communication, essential in everyday life. It includes both spoken and written forms, such as words, phrases, clauses, sentences, and paragraphs, reflecting the diverse cultures of humanity. The study of linguistics is vital for language development, with phonology, morphology, semantics, and syntax each playing a significant role. Semantics, in particular, focuses on the meanings conveyed through speech and writing, which is fundamental for effective communication. Leech (1974) describes meaning as the concept or thought transferred from a speaker to a listener through language. Instagram, a popular social media platform, enhances communication through photos, videos, and captions. Users engage actively by leaving comments, which can be either supportive or critical. This study applies Leech's theory of the seven types of meaning—conceptual, connotative, social, affective, reflective, collocative, and thematic—to examine Instagram captions. Given Instagram's widespread use, especially among college students, its features enable concise message sharing, making it an effective platform for exchanging meanings. Captions add context, express emotions, and convey situational information using various moods and illocutionary acts. This descriptive qualitative study, titled